Use of an enriched inoculum for determination of biodegradable dissolved organic carbon (BDOC) in drinking water - (:unkn) unknown (IWA Publishing, 2009)
The original BDOC procedure requires the use of indigenous bacteria as a seed. Most of the time in original water samples either bacteria are insufficient in numbers or the diversity is not enough to reflect the biodegradable part of DOC. In this study, instead of using the water sample itself as an inoculum as in the original BDOC test, the bacteria originating from the Ömerli reservoir in Istanbul were acclimated in a suspended growth system to remove readily and slowly biodegradable DOC fractions from the reservoir water. This modified BDOC procedure was first tested on standard acetate solutions and later on raw and ozonated waters of the Ömerli reservoir. Additionally, the results of the modified procedure were compared with the original one by also testing the effectiveness of the indigenous seed from the reservoir. In order to determine the most suitable inoculum amount in the modified BDOC procedure, different seeding ratios like 1:100,1:250 and 1:500 (v/v) were tested. In both raw water and ozonated waters, higher BDOC readings were achieved at a seeding ratio of 1:100 than the original procedure. The results showed that the modified procedure resulted in more accurate results compared to the original one and that using an acclimated culture can bring an improvement in BDOC measurement. © IWA Publishing 2009.
Keywords: Biodegradable dissolved organic carbon; Biodegradation; Drinking water; Inoculum